The Influence of American Foreign Policy on Egypt's Domestic Affairs - GUEMARI, Ilyes; GUEDOURI, Shaouki (University of El-oued, 2022)
This dissertation investigates the influence of the American foreign policy On Egypt’s domestic affairs. This research work aims to investigate the motives of American intervention, and to discover the role of U.S. foreign policy in the democratic changes in Arab Spring countries in general and in Egypt specially. Thus, the appropriate research method is the descriptive one in which we attempt to trace the main historical of the American foreign policy his tools in one hand. On the other hand, outcome of these policy are to impose dominance on Egypt because its importance on the Arab region level and the Islamic world. Also, it makes balance between Egypt and Israel for more security in the region through combt terrorism. The results obtained in this present work demonstrate that the American foreign policy in Egypt was for strategic interests and economic reasons. Besides, the results discovered that the United States had an important role in the Arab spring uprisings, using indirect means as the media, religious minorities, and civil society organizations. Moreover, democratic transitions in Egypt and Arab Spring countries resulted in the dissociation of the Arab world as well as the classification of citizens on a sectarian, ethnic, and religious basis. In the end, we suggest some recommendations for Egypt in an attempt to help him resolve their problems which can be treated through the political reform and combat economic corruption for improve separation between the religion and the state as well as getting rid of American and Western domination.
Keywords: Arab Spring, US democracy, Egypt, Foreign Policy